Charting the Ethical Frontier in Newborn Screening Research: Insights from the NBSTRN ELSI Researcher Needs Survey - Yekaterina Unnikumaran; Mei Lietsch; Amy Brower (MDPI AG, 2024)
From 2008 to 2024, the Newborn Screening Translational Research Network (NBSTRN), part of the National Institute of Child Health and Human Development (NICHD) Hunter Kelly Newborn Screening Program, served as a robust infrastructure to facilitate groundbreaking research in newborn screening (NBS), public health, rare disease, and genomics. Over its sixteen years, NBSTRN developed into a significant international network, supporting innovative research on novel technologies to screen, diagnose, treat, manage, and understand the natural history of more than 280 rare diseases. The NBSTRN tools and resources were used by a variety of stakeholders including researchers, clinicians, state NBS programs, parents, families, and policy makers. Resources and expertise for the newborn screening community in ethical, legal, and social issues (ELSI) has been an important area of focus for the NBSTRN and this includes efforts across the NBS system from pilot studies of candidate conditions to public health implementation of screening for new conditions, and the longitudinal follow-up of NBS-identified individuals to inform health outcomes and disease understanding. In 2023, the NBSTRN conducted a survey to explore ELSI issues in NBS research, specifically those encountered by the NBS community. Since NBS research involves collaboration among researchers, state NBS programs, clinicians, and families, the survey was broadly designed and disseminated to engage all key stakeholders. With responses from 88 members of the NBS community, including researchers and state NBS programs, the survey found that individuals rely most on institutional and collegial resources when they encounter ELSI questions. Most survey responses ranked privacy as extremely or very important in NBS research and identified the need for policies that address informed consent in NBS research. The survey results highlight the need for improved collaborative resources and educational programs focused on ELSI for the NBS community. The survey results inform future efforts in ELSI and NBS research in the United States (U.S.) and the rest of the world, including the development of policies and expanded ELSI initiatives and tools that address the needs of all NBS stakeholders.